Nucleoside transport inhibitor, dipyridamole, induced myocardial protection following hemorrhagic shock in ex vivo perfused rat hearts - Soliman, Mona (2011)
INTRODUCTION: Successful protection against post-resuscitation myocardial injury is not available for trauma patients. Whereas intensive improvement in resuscitation strategies reduce myocardial injury, death among trauma patients are among the highest in the world due to myocardial dysfunction and multiple organ failure. Dipyridamole is a nucleoside transport inhibitor. Recent studies have shown that elevation of serum adenosine caused by dipyridamole improve cardiac function. The purpose of the present study was to examine the myocardial protective effects of dipyridamole therapy following 1 h of hemorrhagic shock. METHODS: Sprague–Dawley rats were used. The study consisted of three phases: Phase I to examine the direct effects of dipyridamole on myocardial function by perfusion of the isolated hearts with Krebs Henseleit buffer (KHB) + dipyridamole on the Langendorff apparatus. Phase II examined the protective effects of dipyridamole following 60 min of hemorrhagic shock (HS) by ex vivo treatment with dipyridimole 20 μg/L for 5 min followed by resuscitation with KHB for 55 min. Phase III: 60 min HS followed by in vivo treatment by injecting 1 ml of (20 μg/L) dipyridamole intra-arterially, and resuscitation for 30 min. Myocardial protection was assessed by measuring left ventricular generated pressure (LVGP) and end diastolic pressures (LVEDP). RESULTS: During ex vivo resuscitation, hearts from dipyridamole treated animals had significantly higher LVGP, and significantly lower LVEDP versus controls. CONCLUSION: Dipyridamole therapy produces protection against post-resuscitation myocardial injury in rats.